Effect of hollow fiber membrane packing on the performance of modules formed with fiber tows - Sun, Lili; Panagakos, Grigorios; Lipscomb, Glenn (Separation science and technology, 2025)
Membrane processes are being considered for carbon dioxide capture from concentrated point sources. The processes often use hollow fiber membranes. Modules are formed by gathering fibers together in a bundle. The fibers may be supplied individually or in small groups (i.e. tows) for module fabrication. The use of tows can introduce nonuniform fiber packing due to the size and spacing of the tows. The potential for flow maldistribution and its detrimental effect on module performance is evaluated by solving the governing conservation equations. For the first time, the performance of a module formed from fiber tows is evaluated. Two performance metrics are reported: 1) recovery and 2) required area as a function of carbon dioxide removal. The effects of tow size and tow spacing are evaluated. The results indicate performance is better for smaller tows. Furthermore, lower packings, both intra- and inter-tow, are preferred. The concept of an equivalent planar bundle (EPB) for fiber tow modules is introduced to potentially reduce simulation time and costs. The simple procedure for creating the EPB is validated by comparing the performance metrics calculated using the EPB to the results obtained from full simulations.